The night I disappeared - Deaver, Julie Reece; Copyright Paperback Collection (Library of Congress) (New York : Simon Pulse, 2002)
When Jamie and her mother travel to Chicago so her mother can defend a client, Jamie's world takes a strange turn. Mind slips and vivid daydreams begin to paralyze her as she feels she is slowly losing her mind.
Keywords: Mothers and daughters -- Juvenile fiction; Chicago (Ill.) -- Juvenile fiction; Chicago (Ill.) -- Fiction; Suspense fiction; Young adult fiction